2010
DOI: 10.1007/s12010-009-8882-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Integration Between Reaction and Separation System: Reactive Distillation Process

Abstract: Biodiesel is a clean burning fuel derived from a renewable feedstock such as vegetable oil or animal fat. It is biodegradable, non-inflammable, non-toxic, and produces lesser carbon monoxide, sulfur dioxide, and unburned hydrocarbons than petroleum-based fuel. The purpose of the present work is to present an efficient process using reactive distillation columns applied to biodiesel production. Reactive distillation is the simultaneous implementation of reaction and separation within a single unit of column. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The major bottleneck is known as the cost (75% of the total biodiesel production cost) related to the limited availability of fat or oil resources and also the catalyst choice. 4 Therefore, the replacement of food based feedstocks with inexpensive sources of feedstocks for biodiesel production is more economical than traditional fossil based fuel. 5,6 Simultaneously, nding a prot from the catalytic process is also expected.…”
Section: Introductionmentioning
confidence: 99%
“…The major bottleneck is known as the cost (75% of the total biodiesel production cost) related to the limited availability of fat or oil resources and also the catalyst choice. 4 Therefore, the replacement of food based feedstocks with inexpensive sources of feedstocks for biodiesel production is more economical than traditional fossil based fuel. 5,6 Simultaneously, nding a prot from the catalytic process is also expected.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers showed that the productivity of the reactive distillation column was 6e10 times higher than that of existing conventional processes. Reactive distillation experiments for the synthesis of biodiesel from soybean oil and ethanol using sodium ethoxide were performed by de Lima Da Silva et al [121]. In their experiments, a reactant conversion of 98% was obtained, which verified the technical feasibility of the process.…”
Section: Application To Biorefinery Processesmentioning
confidence: 88%
“…Reactive distillation (RD) is a hybrid process that combines chemical reaction and product separations in a single fractional distillation apparatus (da Silva et al, 2010). Simultaneous separation of reactant and product shifts the equilibrium towards the product side, hence increasing the conversion and selectivity (Estrada-Villagrana et al, 2006; Tuchlenski et al, 2011; Kiss et al, 2012).…”
Section: Reactive Distillation Columnmentioning
confidence: 99%